2021
DOI: 10.3390/brainsci11121625
|View full text |Cite
|
Sign up to set email alerts
|

Body Schema Self-Awareness and Related Dream Content Modifications in Amputees Due to Cancer

Abstract: Purpose: the evaluation of body image perception, pain coping strategies, and dream content, together with phantom limb and telescoping phenomena in patients with sarcoma who underwent surgery for limb amputation. Material and Methods: consecutive outpatients were evaluated at T0 (within 3 weeks after surgery) and T1 (4–6 months after surgery) as follows: demographic and clinical data collection; the Groningen Questionnaire Problems after Arm Amputation; the West Haven-Yale Multidimensional Pain Inventory; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Another direction is that of different types of disabilities or deficiencies. These studies focus on the role of the body schema in psychomotor interventions in children with motor coordination developmental disorders [ 22 , 23 , 24 ], motor deficiencies [ 25 ], amputees [ 26 ], psychiatric disorders [ 27 ], and anorexia nervosa [ 28 ]. School physical education also addresses this topic, especially at the level of primary education [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another direction is that of different types of disabilities or deficiencies. These studies focus on the role of the body schema in psychomotor interventions in children with motor coordination developmental disorders [ 22 , 23 , 24 ], motor deficiencies [ 25 ], amputees [ 26 ], psychiatric disorders [ 27 ], and anorexia nervosa [ 28 ]. School physical education also addresses this topic, especially at the level of primary education [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pragmatical example of the implication of the above presented philosophical perspectives could be offered by phantom limb phenomena. Phantom sensation occurs more intensely on sites with a greater cortical representation (ankle, foot, toes, sole, and heel) but, as well, it changes during movement considering the difference in the distribution of body weight, for example, during the walking practice [155,156]. In the past, the close connection between structure and function was emphasized by Simmel [157] and Price [158], who in examining patients suffering from leprosy found that the lack of the phantom phenomenon may originate from the deficiency of the sensomotoric functions.…”
mentioning
confidence: 99%